Minimal Residual Disease–based Treatment is Adequate for Relapse-prone Childhood Acute Lymphoblastic Leukemia with an intrachromosomal amplification of chromosome 21: The experience of the ALL-BFM 2000 trial - Attarbaschi, A.; Panzer-Grümayer, R.; Mann, G.; Möricke, A.; König, M.; Mecklenbräuker, A.; Teigler-Schlegel, A.; Bradtke, J.; Harbott, J.; Göhring, G.; Stanulla, M.; Schrappe, M.; Zimmermann, M.; Haas, O. A.; on behalf of the Austrian and German ALL-BFM (Berlin-Frankfurt-Münster) Study Group (Klinische Pädiatrie, 2014)
Background: Recently, the UK CCLG and COG reported that an intrachromosomal amplification of chromosome 21 (iAMP21) in acute lymphoblastic leukemia (ALL) loses its adverse prognostic impact with intensified therapy.Patient and Methods: We evaluated the prognosis of iAMP21 among patients from the ALL-BFM (Berlin-Frankfurt-Münster) 2000 trial with 46 of 2 637 (2%) patients iAMP21+.Results: 8-year event-free-survival (EFS, 64±8% vs. 81±1%, p=0.0026) and cumulative incidence of relapse (CIR, 29±8% vs. 14±1%, p=0.008) of the iAMP21 cases were significantly worse compared with non-iAMP21 patients. Within the MRD low-risk group, iAMP21 cases (n=14) had an inferior 8-year EFS (76±12% vs. 92±1%, p=0.0081), but no increased CIR (10±10% vs. 6±1%, p=0.624). Within the MRD intermediate-risk group, iAMP21 cases (n=27) had a worse 8-year EFS (56±11% vs. 78±2%, p=0.0077) and CIR (44±11% vs. 20±2%, p=0.003) with 6/10 relapses occurring after 2 years.Conclusions: Conclusively, we believe that there is no necessity for enrolling all iAMP21 patients into the high-risk arm of ongoing ALL-BFM trials because MRD low-risk patients have a moderate relapse risk under current therapy. Whether the increased relapse risk in MRD intermediate-risk patients can be avoided by late treatment intensification remains to be answered by the AIEOP-BFM ALL 2009 trial randomly using protracted pegylated L-asparaginase during delayed intensification and early maintenance.
Keywords: iAMP21; minimal residual disease; relapse; prognosis